2011
DOI: 10.1038/npp.2011.29
|View full text |Cite
|
Sign up to set email alerts
|

Phasic and Sustained Fear are Pharmacologically Dissociable in Rats

Abstract: Previous findings suggest differences in the neuroanatomical substrates of short-(seconds) vs longer-duration (minutes) fear responses. We now report that phasic and sustained fear can also be differentiated pharmacologically, based on their response to several treatments that either are or are not clinically effective anxiolytics. For these experiments, short-or long-duration clicker stimuli were paired with footshock. Acoustic startle amplitude was later measured in the absence of the clicker, or within seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 70 publications
1
39
0
Order By: Relevance
“…Log transforms of ratio data have been recommended for a variety of reasons, including normalization of skewed distributions prior to parametric analyses (for a concise review, see Keene 1995). Although the results of the analyses included here were not appreciably different for raw ratio vs. log-transformed scores, we include the latter for consistency with prior analyses from our group (Miles et al 2011).…”
Section: Statistical Analysesmentioning
confidence: 94%
See 1 more Smart Citation
“…Log transforms of ratio data have been recommended for a variety of reasons, including normalization of skewed distributions prior to parametric analyses (for a concise review, see Keene 1995). Although the results of the analyses included here were not appreciably different for raw ratio vs. log-transformed scores, we include the latter for consistency with prior analyses from our group (Miles et al 2011).…”
Section: Statistical Analysesmentioning
confidence: 94%
“…4A). Log scores are included as they are often recommended for these types of data (see Keene 1995) and have previously been reported by our laboratory (Miles et al 2011). As the session wore on, potentiation scores of the two groups converged such that the overall difference was not statistically significant.…”
Section: Cannula Tip Placementsmentioning
confidence: 99%
“…For example, Miles et al (2011) demonstrated that both benzodiazepine (chlordiazepoxide) and chronic administration of a serotonin selective reuptake inhibitor (SSRI; fluoxetine) significantly reduced sustained fear responses but had no effect on phasic fear responses. In contrast, the 5HT 1A agonist (buspirone) reduced phasic but not sustained responses, highlighting a pharmacological dissociation.…”
Section: Building Blocks For Human Studies: Current Evidence In Rodenmentioning
confidence: 99%
“…Rats show an enhanced ASR when levels of anxiety are increased (8,30,31). Therefore, we defined molecules as positive (+) for anxiogenic activity when we observed a significant increase in the amplitude of the ASR following exposure.…”
mentioning
confidence: 99%